Consequences and treatment of ovarian failure after total body irradiation for leukaemia. Issue 6714 (16th December 1989) - Cust, M. P.; Whitehead, M. I.; Powles, R.; Hunter, M.; Milliken, S.
Abstract : OBJECTIVE–To assess the incidence and severity of physical and psychosexual symptoms in young women due to ovarian failure caused by total body irradiation for leukaemia and the women's response to hormone treatment. DESIGN–Postal questionnaire and interview. SETTING–Leukaemia unit of oncology hospital. PATIENTS–Consecutive series of 46 English speaking women who had developed ovarian failure after total body irradiation and bone marrow transplantation as treatment for leukaemia. RESULTS–Of the 36 responders, 33 reported some symptoms, vaginal dryness being the most common (29). This profoundly affected sexual function. Although 22 women had had sexual intercourse within six months after treatment, 16 were less interested in and 18 experienced difficulties with sexual intercourse. Anxieties about sterility, femininity, and appearance were common and reduced self confidence. Almost half reported that they had changed their social habits and restricted their social activities. Treatment seemed effective in abolishing symptoms in 24 women, but vaginal dryness remained a problem in three. Two women failed to respond and intercourse remained impossible. CONCLUSIONS–Such patients are vulnerable and access to gynaecologists and endocrinologists soon after treatment would be valuable. The optimal treatment regimen and the long term benefits of treatment have yet to be established.